IHC for Her2 with CBE356 antibody is a more accurate predictor of Her2 gene amplification by FISH than HercepTest™ in breast carcinoma. Issue 10 (27th September 2005) - Ainsworth, R; Bartlett, J M S; Going, J J; Mallon, E A; Forsyth, A; Richmond, J; Angerson, W; Watters, A; Dunne, B
Abstract : Background: Her2 (c-erbB-2/neu) overexpression in breast carcinoma predicts response to the anti-Her2 monoclonal antibody, trastuzumab, and is associated with a poor prognosis. When considering patients for trastuzumab treatment, Her2 protein expression is measured by imunohistochemistry (IHC) and, where staining is equivocal, by fluorescence in situ hybridisation (FISH) detection of Her2 gene amplification. Aims: To compare IHC using CBE356 with IHC using the Food and Drug Administration approved HercepTest™. Methods: CBE356 and HercepTest were analysed using 167 FISH characterised breast carcinomas. Immunohistochemical expression of Her2 was measured semiquantitatively. Sensitivity, specificity, predictive values, and overall accuracy were calculated for both IHC methods using gene amplification by FISH as the end point, and IHC and FISH assays were tested in Kaplan–Meier survival analysis. Results: The accuracy, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of CBE356 positive (2+ and 3+) cases were 94%, 89%, 95%, 84%, and 97%, respectively, and of HercepTest positive (2+ and 3+) cases were 91%, 66%, 98%, 92%, and 91%, respectively. A positive result with CBE356, HercepTest, or FISH was associated with significantly decreased overall survival (log rank p = 0.005, p = 0.0017, and p = 0.0005, respectively). Conclusions: Positive IHC staining for Her2 using CBE356 is 3% more accurate and 23% more sensitive at predicting Her2 gene amplification by FISH than positive staining with HercepTest. Negative IHC using CBE356 antibody is 6% more likely to represent a truly negative result than negative staining with HercepTest. Overall, CBE356 was a more accurate predictor of Her2 gene amplification by FISH than HercepTest.